1977
DOI: 10.2135/cropsci1977.0011183x001700040043x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Recurrent Selection for Specific Combining Ability in Two Open‐pollinated Maize Cultivars1

Abstract: We evaluated recurrent selection for specific combining ability in two open‐pollinated maize (Zea mays L.) cultivars, ‘Kolkmeier’ and ‘Lancaster’. A common, singlecross tester, WF9 ✕ Hy, was used in the first cycle, but inbred Hy was used in the four subsequent cycles. The principal basis of selection was grain yield of half‐sib progenies. Progress for population improvement was evaluated in five environments by measuring yields in the Kolkmeier and Lancaster populations per se, the Hy ✕ Kolkmeier Cn (n = 0, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
1
4

Year Published

1992
1992
2010
2010

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 0 publications
1
31
1
4
Order By: Relevance
“…Gallais (1978) proposed that the tester needed not be a fixed line but (i) it must have a good inherent value and a good value when combined with the reciprocal population and (ii) it must effectively reveal the genetic variability of the reciprocal population. Initial studies showed advantages of RRSi with fixed lines over RRS: greater genetic variance between the test crosses (Darrah et al 1972;Horner et al 1973) and equivalent or greater genetic gains (Horner et al 1973;Russell et al 1973;Walejko and Russell 1977;Zambezi et al 1986;Landi and Frascaroli1995). However, two other studies compared the genetic progress achieved with RRS and RRSi from the same base populations and concluded that RRS was better than RRSi (Russell et al 1992;Menz Rademacher et al 1999).…”
mentioning
confidence: 99%
“…Gallais (1978) proposed that the tester needed not be a fixed line but (i) it must have a good inherent value and a good value when combined with the reciprocal population and (ii) it must effectively reveal the genetic variability of the reciprocal population. Initial studies showed advantages of RRSi with fixed lines over RRS: greater genetic variance between the test crosses (Darrah et al 1972;Horner et al 1973) and equivalent or greater genetic gains (Horner et al 1973;Russell et al 1973;Walejko and Russell 1977;Zambezi et al 1986;Landi and Frascaroli1995). However, two other studies compared the genetic progress achieved with RRS and RRSi from the same base populations and concluded that RRS was better than RRSi (Russell et al 1992;Menz Rademacher et al 1999).…”
mentioning
confidence: 99%
“…Other reports have shown the same results. By using an inbred tester, selection was for specific combining ability (SCA) as well as for general combining ability (GCA) as measured in the performance of the population per se and in crosses with other populations (Russell and Eberhart, 1975;Walejko and Russell, 1977). Hoegemeyer and Hallauer (1976) showed that reciprocal full sib selection in BSIO and BSll was effective for SCA, but that selection for GCA effects was more important.…”
Section: The Larger Genetic Gain In the Bsk(s) Program In Crosses Withmentioning
confidence: 99%
“…Walejko and Russell (1977) evaluated the use of a narrow-based tester to improve two com populations for grain yield. They reported that progress for yield was primarily due to improved general combining ability and that an inbred line could be an effective tester for increasing general combining ability.…”
Section: Literature Review Ihtrapopulaiion Reoirrait Sdectimmentioning
confidence: 99%